Answer:
50 easy
Step-by-step explanation:
Answer:
![130.2845\leq h\leq 137.7245](https://tex.z-dn.net/?f=130.2845%5Cleq%20h%5Cleq%20137.7245)
Step-by-step explanation:
Given an inequality that relates the height h, in centimeters, of an adult female and the length f, in centimeters, of her femur by the equation
![|h - (2.47f + 54.10)| \leq 3.72](https://tex.z-dn.net/?f=%7Ch%20-%20%282.47f%20%2B%2054.10%29%7C%20%5Cleq%20%203.72)
If an adult female measures her femur as 32.25 centimeters, we can determine the possible range of her height by plugging f = 32.25cm into the modelled equation as shown:
![|h - (2.47(32.25) + 54.10)| \leq 3.72\\|h - (79.9045 + 54.10)| \leq 3.72\\|h - (134.0045)| \leq 3.72\\](https://tex.z-dn.net/?f=%7Ch%20-%20%282.47%2832.25%29%20%2B%2054.10%29%7C%20%5Cleq%20%203.72%5C%5C%7Ch%20-%20%2879.9045%20%2B%2054.10%29%7C%20%5Cleq%20%203.72%5C%5C%7Ch%20-%20%28134.0045%29%7C%20%5Cleq%20%203.72%5C%5C)
If the modulus function is positive then:
![h - 134.0045 \leq 3.72\\h \leq 3.71+134.0045\\h\leq 137.7245](https://tex.z-dn.net/?f=h%20-%20134.0045%20%5Cleq%20%203.72%5C%5Ch%20%5Cleq%203.71%2B134.0045%5C%5Ch%5Cleq%20137.7245)
If the modulus function is negative then:
![-(h - 134.0045) \leq 3.72\\-h+134.0045 \leq 3.72\\-h\leq 3.72-134.0045\\-h\leq -130.2845\\](https://tex.z-dn.net/?f=-%28h%20-%20134.0045%29%20%5Cleq%20%203.72%5C%5C-h%2B134.0045%20%5Cleq%203.72%5C%5C-h%5Cleq%203.72-134.0045%5C%5C-h%5Cleq%20-130.2845%5C%5C)
multiply through by -1
![-(-h)\geq -(-130.2845)\\h\geq 130.2845\\130.2845\leq h](https://tex.z-dn.net/?f=-%28-h%29%5Cgeq%20%20-%28-130.2845%29%5C%5Ch%5Cgeq%20130.2845%5C%5C130.2845%5Cleq%20h)
combining the resulting inequalities, the estimate of the possible range of heights will be ![130.2845\leq h\leq 137.7245](https://tex.z-dn.net/?f=130.2845%5Cleq%20h%5Cleq%20137.7245)
Okay lets create an eqn from that information
A first int, B second int, C third int, D fourth int.
B = A + 2
C = A + 4
D = A + 6
A is the smallest integer
B + D = 0.5 (A + C)
Now lets substitute
(A + 2) + (A + 6) = 0.5(A + (A + 4))
now lets dist
2a + 8 = 0.5(2a +4)
2a + 8 = a + 2
a + 8 = 2
a = -6
B = -6 +2
B = -4
C = -6 + 4
C = -2
D = -6 + 6
D = 0
Now using B + D = 0.5(A + C)
-4 + 0 = 0.5(-6 + (-2))
-4 = 0.5 (-8)
-4 = -4
Correct
Therefore, First integer is -6, second integer is -4, third integer is -2 and fourth integer is 0
Answer:
y=54
Step-by-step explanation:
Answer:
x would be 7
Step-by-step explanation:
2x7 = 14
14-3=11!
Hope I could help!
Brainlist??